PENINGKATAN PRESTASI BELAJAR IPA MELALUI METODE DISCOVERY PADA SISWA KELAS VI SDN 2 HARAPAN JAYA - Maryana (Jurnal Evaluasi dan Pembelajaran, 2021)
This study aims to improve achievement and science learning activities with discovery methods in class VI Elementary School 2 Harapan Jaya Bandar Lampung in 2019. This research was conducted in class VI Elementary School 2 Harapan Jaya with a total of 31 students. This action research went through three cycles and 3 meetings per cycle. The use of discovery methods in science learning shows an increasing development of results starting from cycle I to cycle III. In the first cycle learning completeness reached 53%. This is because students still feel new and do not understand what the teacher means and uses by applying discovery learning methods. In the second cycle there was an increase of 24%, namely learning achievement to 77%. In the third cycle it increased by 20% to 97%. Learning activities in cycle I 53%, Cycle II 73%, an increase of 20% and Cycle III 93% or an increase of 20%. The discovery method can improve the achievement and science learning activities of class VI Elementary School 2 Harapan Jaya Bandar Lampung in 2019.